Fiscal Policy and Economic Reconstruction in Latin America. (IMF Working Papers; Working Paper ;, 1989)
This paper surveys the fiscal landscape of Latin America. It analyzes external and domestic factors that over the years led to the deterioration of the fiscal accounts. It also discusses difficulties that are encountered in pursuing a sound fiscal policy under inflationary conditions. Issues such as the connection between external debt and fiscal policy and the role of public investment are also discussed. General guidelines are provided for a fiscal policy for the economic reconstruction of Latin America.